Menggagas Pemilihan Presiden yang Demokratis dan Aspiratif - Rauta, Umbu (Mahkamah Konstitusi Republik Indonesia, 2014)
Since the 2004, election of the president and vice president made directly by the people. Normatively, Indonesia has been striving for election of the president and vice president are more democratic, as reflected through the freedom and the involvement of a political party or coalition of political parties contesting the election to carry the presidential and vice presidential candidates meet all the requirements specified in the legislation. However, in practice the presidential election in 2004 and 2009, found several problems. This paper is intended to identify a number of election issues, once initiated the implementation of a formula for the realization of a more democratic election and aspirative.